The vestibular system in pain and embodiment: cortical overlap, modulatory potential, and therapeutic perspectives - Bouisset, Nicolas; Phylactou, Phivos; Duport, Arnaud (Frontiers in Neuroscience, 2025)
Musculoskeletal pain is increasingly understood as a product of disrupted multisensory integration rather than a direct consequence of tissue damage alone. Among the sensory systems involved in shaping body representation and modulating pain, the vestibular system remains largely overlooked. Beyond its classical role in balance and spatial orientation, vestibular input contributes to embodiment, self-location, and bodily self-consciousness—processes that are frequently altered in chronic pain conditions. Neuroimaging and clinical evidence reveal a striking overlap between vestibular integration regions and the so-called pain neuromatrix, suggesting shared cortical substrates for vestibular and nociceptive/pain processing. Moreover, vestibular dysfunction is associated with disembodiment phenomena such as depersonalization and derealization, which mirror sensory distortions observed in chronic pain syndromes. Experimental studies demonstrate that vestibular stimulation—via caloric or electric modalities—can modulate pain perception, influence somatosensory integration, and recalibrate distorted body representations. This perspective paper synthesizes current findings at the intersection of vestibular neuroscience, pain modulation, and embodiment, proposing that the vestibular system could constitute a critical but underrecognized component in musculoskeletal health. Incorporating vestibular pathways into pain models may, therefore, improve our understanding of chronicity and open novel therapeutic avenues for neuromodulation.